If it's not what You are looking for type in the equation solver your own equation and let us solve it.
110=11(m+5)
We move all terms to the left:
110-(11(m+5))=0
We calculate terms in parentheses: -(11(m+5)), so:We get rid of parentheses
11(m+5)
We multiply parentheses
11m+55
Back to the equation:
-(11m+55)
-11m-55+110=0
We add all the numbers together, and all the variables
-11m+55=0
We move all terms containing m to the left, all other terms to the right
-11m=-55
m=-55/-11
m=+5
| 28=z+208/17 | | -46+9x=74+x | | n-7=2.2 | | -25=-5-5x | | 2+4x+3x-5x=14 | | 25(n=8)=850 | | 10x=5x+250 | | j/5+28=37 | | 7y+5+2(9y)=180 | | j+107/28=7 | | 5n-8=41 | | 44=78-u | | 16=f+105/12 | | 95x=2710 | | n/9-10=6 | | 10x-11=9x | | b3.5=7.3 | | 9(x-3)=30 | | 2b-17+3b-8+b+19=180 | | 6x+15-8=12x+24 | | 104=456-z | | Y=130x+100 | | 16=2(t+3) | | n=53/5=21 | | 29-k=2 | | 3x+34=6x+25 | | r+17=43 | | 54/v=9 | | n+252/12=31 | | 63k−(k+4)=4(k−2)−6 | | 14(t+46)=840 | | n-(-1)=-1 |